Radioterapia w starczym zwyrodnieniu plamki związanym z wiekiem (AMD). Opis przypadku - Puchalska-Niedbał, Lidia; Sylwestrzak, Zofia; Jarema, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The radiotherapy is worth to remember in the most progression causes of AMD, when there is no possibility for application the modern methods of the treatment. We present cause of patient with bilateral advanced changes and low visual acuity in course AMD, who had applied rtg therapy and laser fotocoagulation. The right eye was radiated with foton beam energy 10 MeV using linear accelerator. Dosage of 9 Gy was delivered in 3 fractions through 5 days. In right eye we observed increase of visual acuity from 2/50 before treatment to 3/50 after 12 months, and 0.1 after the 48 months of radiation. The visual acuity in the left eye decreased from 0.2 to 2/50 after the 48 months. The improvement of acuity vision after rtg therapy allowed the patient self-dependence life.